Understanding the factors influencing biosecurity adoption on smallholder poultry farms in Ghana: a qualitative analysis using the COM-B model and Theoretical Domains Framework - Buckel, Anica; Afakye, Kofi; Koka, Eric; Price, Cortney; Kabali, Emmanuel; Caudell, Mark A. (Frontiers in Veterinary Science, 2024)
Antimicrobial resistance (AMR) poses a significant global threat to public, animal, and environmental health, consequently producing downstream economic impacts. While top-down approaches to addressing AMR (e.g., laws regulating antimicrobial use) are common in high-income countries, limited enforcement capacities in low-and middle-income countries highlight the need for more bottom-up approaches. One such bottom-up approach within agriculture promotes on-farm biosecurity, thereby reducing the need for antimicrobials by mitigating disease risk and limiting AMR transmission. Efforts to understand producers' uptake of biosecurity practices, or lack thereof, have drawn upon behaviour change models that measure the intention of a producer to adopt biosecurity practices. However, a growing body of literature shows that intention, and by extension, knowledge and awareness, are insufficient predictors of behaviour, thereby giving rise to a knowledge-action gap. To understand the barriers and enablers patterning the intention-action gap in biosecurity, we draw upon models from Behavioural Science. We analysed 15 in-depth interviews and two focus group discussions with smallholder poultry producers in Ghana to understand factors underlying the intention-action gap in adopting biosecurity. As an analytical framework, we draw upon the Theoretical Domains Framework (TDF) in combination with the Capacity-Opportunity-Motivation Behaviour Model (COM-B). We conclude that all factors across the COM-B spectrum must be considered when designing and implementing behaviour change interventions, emphasizing the need for more interdisciplinary collaboration. Recommendations and implications for both researchers and applied practitioners from the veterinary and social and behavioural sciences are discussed.